Analysis of the Needs for the Development of Interactive Multimedia Based on Augmented Reality in Physics Learning - Risky SissyLia; Sardianto Markos Siahaan; Apit Fathurohman (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the Study: This study investigates the initial needs of teachers for the development of interactive multimedia based on Augmented Reality (AR) for physics education, specifically in the context of kinetic gas theory. As part of development research at the preliminary study stage, the goal is to design innovative teaching tools that simplify complex physics concepts and enhance student engagement. Methodology: A survey-based research design was adopted, with data collected via questionnaires distributed to middle and high school physics teachers using the Google Form platform. The study examined teacher perspectives on AR-based learning media's necessity, usability, and potential impact in their classrooms. Main Findings: The results revealed a strong demand among physics teachers for AR-based interactive multimedia, highlighting its potential to address the challenges of teaching physics concepts often perceived as abstract and complex by students. Teachers emphasized the need for tools that make the learning process more engaging, interactive, and relatable. The findings also indicated that AR-based multimedia offers a promising solution, aligning with the growing integration of digital technology in education. Teachers noted that AR tools could increase efficiency, foster active learning, and cater to diverse learning styles, making physics more accessible and enjoyable. Novelty/Originality of the Study: This study contributes to the growing field of digital education by emphasizing the application of AR technology in physics learning. It provides a novel perspective on how AR can bridge the gap between theoretical physics and practical understanding, fostering curiosity and deeper comprehension.